2020
DOI: 10.1038/s41467-020-19291-x
|View full text |Cite
|
Sign up to set email alerts
|

Proline rich 11 (PRR11) overexpression amplifies PI3K signaling and promotes antiestrogen resistance in breast cancer

Abstract: The 17q23 amplicon is associated with poor outcome in ER+ breast cancers, but the causal genes to endocrine resistance in this amplicon are unclear. Here, we interrogate transcriptome data from primary breast tumors and find that among genes in 17q23, PRR11 is a key gene associated with a poor response to therapeutic estrogen suppression. PRR11 promotes estrogen-independent proliferation and confers endocrine resistance in ER+ breast cancers. Mechanistically, the proline-rich motif-mediated interaction of PRR1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 59 publications
2
47
2
Order By: Relevance
“…Interestingly, a similar result from cell cycle evaluation was observed in our research. Besides, cancer drug resistance also positively correlates with PRR11 expression level according to Lee et al's research [ 16 ], which may cause patients' poor prognosis. PRR11 has been proven to hold prognostic values and take a role as a carcinogenic factor in BC [ 17 ] (our bioinformatics prediction showed that patients with high expression of PRR11 suffered poor prognosis).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a similar result from cell cycle evaluation was observed in our research. Besides, cancer drug resistance also positively correlates with PRR11 expression level according to Lee et al's research [ 16 ], which may cause patients' poor prognosis. PRR11 has been proven to hold prognostic values and take a role as a carcinogenic factor in BC [ 17 ] (our bioinformatics prediction showed that patients with high expression of PRR11 suffered poor prognosis).…”
Section: Discussionmentioning
confidence: 99%
“…As application of subcutaneous model has advantage in monitoring the growth of tumor, tumor growth curve detection and evaluation of drug efficacy ( Masuelli et al, 2017 ; Ireson et al, 2019 ; Lee et al, 2020 ), we chose subcutaneous model to evaluate the inhibition effect by knocking down C1QBP or shC1QBP combined with PTX treatment. For the subcutaneously injected group, the volumes of tumors formed by the control cells were significantly greater than those from cells expressing lower levels of C1QBP ( Figure 3C ), suggesting that silencing C1QBP restrained cell proliferation in mice.…”
Section: Resultsmentioning
confidence: 99%
“…The expression of PRR11 is closely related to tumorigenesis, progression and poor prognosis in cancers, including lung, gastric, pancreatic, breast, esophageal and ovarian cancers [15,[29][30][31][32][33]. PRR11 was also demonstrated to promote anti-estrogen resistance in breast cancer by amplifying the PI3K signaling pathway [34]. Additionally, PRR11 activated the Akt/mTOR autophagy signaling pathway to facilitate tumorigenesis in non-small cell lung cancer, suggesting that this gene may affect cancer cells through different signal transduction pathways.…”
Section: Discussionmentioning
confidence: 99%